LIBRARY LEADERSHIP AND MANAGEMENT STYLES: A COMPARATIVE STUDY - Jagmohan Meena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study explores various leadership and management styles employed by library leaders in academic, public, and special libraries. It examines how these styles influence the operational efficiency, staff motivation, decision-making processes, and overall performance of libraries. The study employs a comparative approach, analyzing different leadership theories such as transformational, transactional, and laissez-faire leadership. The research reveals that leadership styles significantly impact library culture, innovation, staff development, and service delivery. Recommendations are made for adopting leadership styles that best suit modern library challenges in the digital era.